Variability of physiological indicators of resistance to salinity between genotypes of dwarf and giant cashew - Ponte, Luiz Ferreira Aguiar; Ferreira, Osnan Soares; Alves, Francisco Abel Lemos; Ferreira‑Silva, Sérgio Luiz; Pereira, Vanda Lúcia Arcanjo; da Silveira, Joaquim Albenísio Gomes (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the resistance to salinity of cashew genotypes from dwarf and giant groups, with seedlings in pregrafting phase, using physiological indicators. Germination and seedling initial growth of ten rootstock genotypes were evaluated under two salinity conditions: substrate irrigated with distilled water or with 50‑mmol L-1 NaCl solution, until the eight mature leaves stage (28 days after sowing). The seedlings were irrigated with Hoagland & Arnon nutrient solution, for ten more days. Physiological indicators of resistance – Na+ and K+ contents and K+/Na+ relation, in leaves and roots – did not differ between genotypes, in the absence or presence of salinity. The indicators and prolin contents were not correlated to the accumulated mass in roots and leaves. Under salinity conditions, the genotypes from the dwarf group showed higher root mass in comparison to those from the giant group, which had greater mass allocation in leaves. There was low genetic variability within each group. Regarding root and leaf growth, there was variability between groups, in both salinity conditions.